Omega-3 fatty acids, lipoprotein-associated phospholipase A₂ and oxidized LDL in glucose sensitive and glucose intolerant males and females - Dhara, Jerusa, author; Nelson-Ceschin, Tracy L., advisor; Bizeau, Michael, committee member; Hickey, Matthew S., committee member (Colorado State University. Libraries, 2010)
Lp-PLA2 is a novel inflammatory marker that has been proposed as an independent risk marker for cardiovascular disease. Lp-PLA2 in circulation is principally bound to low-density lipoprotein cholesterol (LDL-C) in humans and the substrate for the enzyme is provided by the oxidized phospholipid component of LDL-C. In the present study, plasma levels of Lp-PLA2 concentration, activity and plasma levels of oxidized LDL were measured in fifty-nine weight stable adults, mean age 61 years, at baseline and following an 8-week supplementation of ALA, EPA+DHA or control (olive oil). Additionally, glucose, LDL-C, HDL-C, triglycerides and insulin levels were measured at baseline and following the intervention. Fasting blood glucose was measured for the purpose of assessing changes between glucose intolerant and glucose sensitive individuals. Results showed that there was no significant change in the concentration or activity of Lp-PLA2 either in low ox-LDL group or high ox-LDL group after ALA or EPA/DHA supplementation in diet. No particular trend was observed, however, a slight decrease in Lp-PLA2 concentration in all the three groups (CON, ALA, and EPA/DHA) was seen in higher ox-LDL group. But Lp-PLA2 activity only decreased in ALA group (Baseline=163.42 mmol/min/mL + 27.29; week 8 =143.25 mmol/min/mL+14.52) in high ox-LDL group. A minor increase in Lp-PLA2 concentration in the control group (baseline= 206 ng/mL +62.29; week 8= 215.01 ng/mL+73.26) in low ox-LDL group and a slight decrease in Lp-PLA2 activity in control group was observed (baseline= 137.97 mmol/min/mL+ 27.50; week 8= 133.92 mmol/min/mL+28.56). There were no significant changes in fasting plasma ox-LDL after the diet supplementation in any of the groups, but a decreasing trend in LDL-C was observed. In glucose sensitive subjects, a positive correlation between Lp-PLA2 activity and ox-LDL is seen at p<0.01 level. The results of this study also do not represent a baseline significant relation between Lp-PLA2 concentration and activity and ox-LDL in glucose intolerant subjects. The results support the view that Lp-PLA2 is associated with ox-LDL, but do not provide any evidence that omega-3 fats mediate the inflammatory process via Lp-PLA2 or ox-LDL.
Department Head: Richard Gay Israel.